2016
DOI: 10.5812/traumamon.35303
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Survival and Hospital Care Quality in Patients with Traffic Injury in East Azerbaijan

Abstract: Background: Traffic events are the second most common cause of mortality and the first cause of years of life lost (YLL) in Iran. Objectives: The aim of this study was to determine the survival of patients with traffic injury and evaluate hospital care quality using the trauma and injury severity score (TRISS) method. Methods: This cross-sectional study was conducted on 1000 patients aged 1 to 89 years old who were hospitalized in two university hospitals in East Azerbaijan, Iran. Patients were selected by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…It has been noticed that the rate of mortalities caused by accidents was associated with the quality of hospital services. In this regard, the results of the current study are consistent with other investigations (15,22,23). The measured indices explain the role of immediate service provision for the victims and hospital service quality in the survival and recovery of traffic accident patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It has been noticed that the rate of mortalities caused by accidents was associated with the quality of hospital services. In this regard, the results of the current study are consistent with other investigations (15,22,23). The measured indices explain the role of immediate service provision for the victims and hospital service quality in the survival and recovery of traffic accident patients.…”
Section: Discussionsupporting
confidence: 93%
“…In a study carried out by Deshmukh et al (21) in India, it was observed that the number of mortalities is five cases greater than the results of the MTOS. The studies conducted by Esmaili et al (22) and Khosravi et al (23) showed seven and four mortalities higher than the MTOS findings, respectively. All of the aforementioned studies associated the low quality of hospital services with a high number of mortalities (24)(25)(26).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Among the various types of trauma, trauma caused by a crash is a life-threatening condition for all age groups [ 8 ]. Traffic injuries are reported to have increased from 999,000 in 1990 to more than one million deaths in 2002, and were predicted to reach about two million deaths by 2020 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%